1998
DOI: 10.1093/brain/121.8.1469
|View full text |Cite
|
Sign up to set email alerts
|

Axonal damage correlates with disability in patients with relapsing- remitting multiple sclerosis. Results of a longitudinal magnetic resonance spectroscopy study

Abstract: It has been difficult to establish a strong correlation between total brain T2-weighted lesion volume on MRI and clinical disability in multiple sclerosis, in part because of the lack of pathological specificity of T2-weighted MRI signal changes. Proton magnetic resonance spectroscopy studies have shown that measurements of the resonance intensity of N-acetylaspartate (which is localized exclusively in neurons and neuronal processes in the mature brain) can provide a specific index of axonal damage or dysfunct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
242
2
8

Year Published

2001
2001
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 459 publications
(271 citation statements)
references
References 46 publications
19
242
2
8
Order By: Relevance
“…Adenosine-mediated anti-inflammatory effects have been studied chiefly in macrophage-like cells, with inhibitory effects on cytokine, chemokine, and MMP release (Le Moine et al, 1996;De Stefano et al, 1998). Macrophage/microglial infiltration and activation are key features of EAE in the present A1AR null mouse model.…”
Section: Discussionmentioning
confidence: 92%
“…Adenosine-mediated anti-inflammatory effects have been studied chiefly in macrophage-like cells, with inhibitory effects on cytokine, chemokine, and MMP release (Le Moine et al, 1996;De Stefano et al, 1998). Macrophage/microglial infiltration and activation are key features of EAE in the present A1AR null mouse model.…”
Section: Discussionmentioning
confidence: 92%
“…Nevertheless, further studies including morphometry of muscle fibers and immunohistological investigations of several intermediate filaments in skeletal muscles are needed. Thus, clinical signs of affected mice are most likely caused by axonal damage, which is regarded as the major pathological correlate of permanent functional deficits (De Stefano et al 1998;Trapp et al 1998;Kornek et al 2000;Coleman 2005). However, chromatolysis of neurons may have caused additional secondary axonal damage.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, remyelination is typically incomplete and ultimately fails in the setting of recurrent episodes contributing to the progressive demyelination, gliosis, axonal damage, and neurodegeneration typically noted in MS [66,67]. Several studies have indicated that axonal pathology is the best correlate of chronic neurological impairment in MS and its animal model, experimental autoimmune encephalomyelitis (EAE) [68][69][70][71][72][73].…”
Section: Myelin Regeneration Fails In Msmentioning
confidence: 99%